2017
DOI: 10.21849/cacd.2017.00171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lexical Retrieval Cascade Treatment on Naming and Discourse of Individuals with Logopenic Variant of Primary Progressive Aphasia (lvPPA)

Abstract: ABSTRACT. This study provided a systematic review on nonpharmacological interventions applied to patients diagnosed with Primary Progressive Aphasia (PPA) and its variants: Semantic (SPPA), Nonfluent (NFPPA) and Logopenic (LPPA) to establish evidence-based recommendations for the clinical practice of cognitive rehabilitation for these patients. Methods: A PubMed and LILACS literature search with no time restriction was conducted with the keywords PPA (and its variants) AND rehabilitation OR training OR interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Regarding the long-term maintenance of effects, lexical retrieval treatment [65,66,[76][77][78][79][80][81][82][83][84] and semantic treatment [56, 61, 74, 89, 91-93, 95, 97-99, 101, 103, 105] generally produce maintained effects over time without differences between subtypes of PPA. In contrast, only one study evaluated the maintenance of gains after phonological and orthographic treatment in nf/avPPA, svPPA and l/phvPPA and recorded improvement maintenance at follow-up only in svPPA patients [72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the long-term maintenance of effects, lexical retrieval treatment [65,66,[76][77][78][79][80][81][82][83][84] and semantic treatment [56, 61, 74, 89, 91-93, 95, 97-99, 101, 103, 105] generally produce maintained effects over time without differences between subtypes of PPA. In contrast, only one study evaluated the maintenance of gains after phonological and orthographic treatment in nf/avPPA, svPPA and l/phvPPA and recorded improvement maintenance at follow-up only in svPPA patients [72].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, two studies have reported evidence of lexical retrieval treatment only in subjects with a diagnosis of nf/avPPA [66,76], three only in patients with svPPA [65,75,78] and two only in patients with l/ phvPPA [80,81]. The other six studies included participants with different variants of PPA, such as nf/avPPA, svPPA, l/phvPPA and mixed PPA [18,77,79,[82][83][84] and aimed to examine the effects of lexical retrieval treatment on oral and/or written naming abilities by comparing different subtypes of PPA.…”
Section: Lexical Retrieval Treatmentmentioning
confidence: 99%
“…Cueing hierarchy techniques have shown promising item generalization in some studies 9,48 but not others. 39,40 Generalization to untreated tasks (object description and naming to description, 33,41 semantic feature verification 58 ) has been reported following COEN training with individuals with svPPA. Other individuals with svPPA demonstrated generalization of treatment for partially known items using a Look, Listen, Repeat technique 28 to untreated tasks including video description, word-picture matching, and-importantly in respect to the benefit of the treatment for everyday life-to actions in response to household requests (e.g., Can you bring me two plates?).…”
Section: Generalization Of Treatment Gains To Untrained Items Tasksmentioning
confidence: 99%
“…34 We can compare these results with those obtained using Lexical Retrieval Cascade, 9 a well-described cueing hierarchy technique that has also been investigated in several studies. 39,40 Small sets of approximately five or six items are treated intensively in each session, with the participants moving onto a new set when they reach a predetermined accuracy criterion (e.g., 80% correct). Lexical Retrieval Cascade studies show immediate gains after only a few sessions of treatment, a frequently reported pattern; 50,51 thus, over successive sessions, new sets can be introduced and mastered.…”
Section: Comparison Of Lexical Retrieval Treatment Techniques Across mentioning
confidence: 99%
See 1 more Smart Citation